Systems Thinking and Arts Integration Through Library Educational Programming on a STEM Campus. Issue 2 (2nd October 2019) - Valk, Alison
Abstract: Librarians have moved beyond traditional information literacy instruction to an environment in which they create strong partnerships with the campus faculty, community, and beyond. The article addresses these specialized partnerships in a unique library program, providing an overview of newly formed educational initiatives at the Georgia Tech Library. This article discusses the genesis of the Communication through Art program (http://art.library.gatech.edu ), how it was structured, how the program expanded, how projects were designed, future implications, and the methods of assessment. This program brings librarians, artists, campus educators, and community members together in course project design and implementation.